Lymphaticovenous Bypass for Immediate Lymphatic Reconstruction in Locoregional Advanced Melanoma Patients - Cakmakoglu, Cagri; Kwiecien, Grzegorz J.; Schwarz, Graham S.; Gastman, Brian (Journal of Reconstructive Microsurgery, 2020)
Background Extremity lymphedema is a dreaded complication of ilioinguinal or axillary lymphadenectomy. In conventional lymph node dissection, no effort is performed to maintain or reestablish extremity lymphatic circulation. We hypothesized that immediate lymphatic reconstruction (ILR) could be a reproducible procedure to maintain functional lymphatic flow after ilioinguinal and axillary lymphadenectomy in patients with malignant melanoma. This is the first report describing prophylactic ILR in patients with melanoma who underwent complete lymph node dissection for gross nodal disease.Patients and Methods We report a case series of 22 malignant melanoma patients who had axillary or ilioinguinal lymph node dissection for bulky locoregional invasion with immediate lymphatic reconstruction. A novel method to identify and select lymphatics with high flow using fluorescent lymphangiogram with indocyanine green dye gradient software is described. Surgical details, common difficulties, as well as indications are discussed. Instructional videos are also provided.Results Our technique is reproducible, since we have successfully completed immediate lymphatic reconstruction in 22 cases consecutively. Intradermal indocyanine green injections allowed for visualization of 1 to 3 transected lymphatics after lymphadenectomy. An average of 1.8 lymphaticovenous bypass (range 1–3) was performed per patient.Conclusion Reestablishment of lymphatic circulation after ilioinguinal or axillary lymphadenectomy in patients with melanoma characterizes a novel method that may reduce the problem of upper and lower extremity iatrogenic lymphedema. This is particularly important given the emergence of new adjuvant treatment modalities that considerably improve patients' survival after lymphadenectomy.
Keywords: lymphedema; lymphaticovenous bypass; lymphadenectomy; melanoma; lymph node dissection; lymphaticovenular anastomosis